2015
DOI: 10.1111/mmi.13030
|View full text |Cite
|
Sign up to set email alerts
|

Diverse supramolecular structures formed by self‐assembling proteins of the Bacillus subtilis spore coat

Abstract: SummaryBacterial spores (endospores), such as those of the pathogens C lostridium difficile and B acillus anthracis, are uniquely stable cell forms, highly resistant to harsh environmental insults. B acillus subtilis is the best studied spore‐former and we have used it to address the question of how the spore coat is assembled from multiple components to form a robust, protective superstructure. B . subtilis coat proteins (CotY, CotE, CotV and CotW) expressed in E scherichia coli can arrange intracellularly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 69 publications
5
68
0
Order By: Relevance
“…3a 2 , white arrows) were measured in a range from 40 to 90 nm (n = 20). These results are in good agreement with electron micrographs of typical CotE aggregates, displaying extended net-like structures (Jiang et al, 2015). However, the average repeat spacing was about 15 nm, although the mesh size was highly variable.…”
Section: Assembly Of Cote and Cotz On Silicon Substrate In Vitrosupporting
confidence: 84%
“…3a 2 , white arrows) were measured in a range from 40 to 90 nm (n = 20). These results are in good agreement with electron micrographs of typical CotE aggregates, displaying extended net-like structures (Jiang et al, 2015). However, the average repeat spacing was about 15 nm, although the mesh size was highly variable.…”
Section: Assembly Of Cote and Cotz On Silicon Substrate In Vitrosupporting
confidence: 84%
“…Figure B shows that both heat and reducing agent are required for the complete loss of detectable hexamer. We previously found analogous behaviour for CotY Bs hexamers and showed that higher order assemblies also required reducing agent for disassembly (Jiang et al ., ). Treatment of rExsY crystals with a combination of both heat and DTT was required to destroy any ordered crystallinity.…”
Section: Discussionmentioning
confidence: 97%
“…Our studies of coat proteins in B. subtilis suggest that self‐organization plays a very significant role in spore construction (Jiang et al ., ). Does self‐assembly play a role in the extension of the exosporium around the nascent spore?…”
Section: Introductionmentioning
confidence: 97%
“…These proteins form one-dimensional fibers, two-dimensional sheets, and three-dimensional stacks. With CotY, the mode of assembly resembles that of the exosporium basal layer described for B. anthracis and B. cereus (55). CotY is a component of the B. subtilis crust layer and the B. cereus group exosporium layer.…”
Section: The Spore Crust Layermentioning
confidence: 99%
“…Interestingly, the CotZ protein, which plays a role in the assembly of the crust layer of B. subtilis, displays sequence similarity to the ExsY protein (35% identity and 46% similarity over 141 residues), a protein involved in exosporium assembly in B. anthracis (42). B. subtilis CotE, CotV, CotY, and CotW coat proteins expressed in Escherichia coli can self-assemble intracellularly into stable complexes (55). These proteins form one-dimensional fibers, two-dimensional sheets, and three-dimensional stacks.…”
Section: The Spore Crust Layermentioning
confidence: 99%